Plasmonic properties of coupled metal wires in the cluster with triangular or square configuration - Stognii, N. P.; Sakhnenko, N. K. (IEEE, 2015)
This paper presents a theoretical investigation and a straightforward analysis of the plasmonic properties of coupled metal wires in the cluster with triangular or square configuration. Solution of the eigenvalue problem in form of matrix equations is received. Eigenoscillationg frequencies and quality factors of the nanowires of such configurations are studied. Possibility of quality factor enhancement in optimized assemble configurations has been demonstrated.
Keywords: plasma; surface plasmons; plasmon resonances; eigenfrequency; cluster